A introductión to English Morphology ; Words and Their Structure. - Carstairs-McCarthy, Andrew (Edinburgh University Press, 2018)
What exactly are words? Are they the things that get listed in dictionaries, or are they the basic units of sentence structure? Andrew Carstairs-McCarthy explores the implications of these different approaches to words in English. He explains the various ways in which words are related to one another, and shows how the history of the English language has affected word structure.Topics include: words, sentences and dictionaries; a word and its parts (roots and affixes); a word and its forms (inflection); a word and its relatives (derivation); compound words; word structure; productivity; and the historical sources of English word formation. Features: * presupposes no linguistic training * aimed at students of English (literature or language) and also provides a sound basis for further linguistic study * contains ample exercise material, with answers and discussion, which can serve as models for further exercises